Možnosti recyklace odpadů tvrdých PU pěn z produkce KingSpan CZ - Figalla, Silvestr (Vysoké učení technické v Brně. Fakulta chemická, 2011)
Teoretická část bakalářské práce zhodnocuje metody a trendy recyklace polyuretanových materiálů s důrazem na tvrdé polyuretanové pěny používané jako termoizolace ve stavebnictví. Experimentální část práce je zaměřena na ověření využitelnosti glycerolu jako alkoholyzačního činidla v procesu regenerace polyolu v kombinaci s perspektivním mikrovlnným ohřevem reakční směsi. V závěru práce jsou navrženy další kroky k rozvoji uvedeného procesu s cílem převedení metody do technické praxe.

The theoretical part of the bachelor thesis evaluates methods and trends of recycling polyurethane materials with the emphasis on rigid polyurethane foams used as thermo isolation building material. The experimental part is focused on glycerol process verification as an alcoholization agent in the regenerative process of polyol, together with perspective microwave heating of reaction mixture. The final part of the work suggests further steps in the development of above mentioned process with the aim of its transforming into technical practice.
Waste Recycling Possibilities of Rigid PU Foams from the Production of KingSpan CZ
Keywords: Recyklace polyuretanů; polyuretanová pěna; alkoholýza; glycerolýza; zkapalnění; glycerol; mikrovlnný ohřev; Polyurethane recycling; rigid polyurethane foam; liquefaction; alcoholysis; glycerolysis glycerol; microwave heating